Digital Flipbook Imunopedia (DFI): A Development in Immune System e-Learning Media - Rizhal Hendi Ristanto (International Journal of Interactive Mobile Technologies, 2020)
Immune system content along with body defense mechanism tends to be an abstract content that is hard to comprehend by students. Digital flipbook learning media become an innovative learning medium to facilitate the immune system content understanding for students. Method used in the research is ADDIE research and development with the following stages: analysis, define, design, implement, and evaluation. The research is limited to the development stage. The number of respondents in the research consists of 30 senior high school students aged 17-19 years and 3 (three) Biology teachers aged 30-40 years for needs analysis. Learning media expert validation includes 3 (three) teachers and ten students for small group test. The medium is developed using applications of Microsoft PowerPoint 2010, Movavi Video Editor 14 and Flip PDF Professional. The assessment results of Digital Flipbook Imunopedia (DFI) learning media development by the three Biology education experts indicate valid and feasible to be used in immune system learning process. Average of each feasibility test aspect is content aspect (3.05), media aspect (2.95), and language aspect (2.95). The trial test results to small group regarding the DFI content, display, and benefits indicate a very feasible criterion (3.62).